2021
DOI: 10.3389/fimmu.2021.670040
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A, ARID1B, and ARID2 Mutations Serve as Potential Biomarkers for Immune Checkpoint Blockade in Patients With Non-Small Cell Lung Cancer

Abstract: Worldwide, non-small cell lung cancer (NSCLC) has the highest morbidity and mortality of all malignancies. The lack of responsiveness to checkpoint inhibitors is a central problem in the modern era of cancer immunotherapy, with the rapid development of immune checkpoint inhibitors (ICIs) in recent years. The human switch/sucrose nonfermentable (SWI/SNF) chromatin-remodeling complex has been reported to be recurrently mutated in patients with cancer, and those with SWI/SNF mutations have been reported to be sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…In our institutional study of 1162 Chinese patients with NSCLC, we reported a mutational incidence rate of 20% in SWI/SNF genes. Consistent with previous studies, 9,11,19,20 SWI/SNF-mut was correlated with older age, smoking, male sex, higher TMB, and higher proportion of PD-L1-positive. Moreover, SWI/SNF-mut was more often observed in tumors with advanced disease, bone, and liver metastasis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our institutional study of 1162 Chinese patients with NSCLC, we reported a mutational incidence rate of 20% in SWI/SNF genes. Consistent with previous studies, 9,11,19,20 SWI/SNF-mut was correlated with older age, smoking, male sex, higher TMB, and higher proportion of PD-L1-positive. Moreover, SWI/SNF-mut was more often observed in tumors with advanced disease, bone, and liver metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…7,8 In NSCLC, ARID1A, and SMARCA4 were the most frequently mutated genes, which occur in 8% to 9% of patients. [8][9][10][11] The impact of SWI/SNF gene mutations on the efficacy of immune checkpoint inhibitors (ICIs) in NSCLC has recently drawn considerable attention. A retrospective study among 292 NSCLC patients treated with ICIs found that patients with SMARCA4 alterations had improved overall survival (OS) (hazard ratio [HR], 0.67; p = 0.01).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has suggested that the epigenetic alterations caused by chromatin mediators, such as chromatin remodelers, cooperatively drive tumor progression and immunotherapy resistance [ 159 ]. For instance, the mutations in several of the chromatin remodeler encoding genes, such as ARID1A, ARID1B, and ARID2, have been confirmed to be more likely to benefit from immune checkpoint blockade therapy for NSCLC patients [ 160 , 161 ]. Another recent study has further delineated the tumor-promoting role of the SWI/SNF component SMARCC1 in HCC.…”
Section: Effects Of Chromatin Remodeler Deregulation On Cancer Progre...mentioning
confidence: 99%
“…Knowledge of chromatin remodeling in the regulation of immunotherapies, especially the immune checkpoint inhibitors (ICIs) in cancer, has yielded several promising therapeutic strategies that show great benefits to patients. Genetic alterations in ARID family members have been revealed to be related to sensitivity to ICI therapy in cancer [ 211 ], such as in NSCLC [ 160 ], EBV-positive gastric cancers [ 212 ], and ovarian cancer ( Figure 4 ) [ 213 , 214 ]. For example, ARID1A alters sensitize tumors to immune checkpoint blockade, suggesting a potential candidate for immunotherapy [ 215 ].…”
Section: Targets For Cancer Therapymentioning
confidence: 99%